Transformation of Character Education Through Implementation of Local Wisdom Values in Madrasah - Firman Sidik; Herson Anwar; Istianah Masruroh Kobandaha (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to examine the transformation of character education by implementing local wisdom values in Madrasah Ibtidaiyah Negeri 1 Gorontalo City. This research uses a qualitative type, where data is collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusions drawn. The study results show that character education is transformed through implementing local wisdom values, such as huyula, which are integrated into character education through three main strategies: internalization of values, integration in learning, and habituation through daily practice. The values of local wisdom are introduced cognitively, internalized affectively, and manifested in students' actions. This transformation shows that character education based on local wisdom can sustainably shape the students' social attitudes, care, and cooperation. In addition, this approach proves the effectiveness of contextual pedagogy in bridging the values of local wisdom, religious teachings, and national educational goals. Therefore, the integration of local wisdom values ​​in character education needs to be strengthened and replicated in the context of education in all aspects to provide significant scientific contributions in the development of character education studies based on local wisdom. This finding also strengthens the understanding that integrating local wisdom values ​​, such as cooperation, can be a contextual and relevant foundation in shaping students' character.